Analyzing dead core formation in catalyst pellets of various geometries under non-isothermal conditions - M. Menaka; R. Manimaran; S. Saravanakumar; L. Rajendran; A. Eswari (Partial Differential Equations in Applied Mathematics)
This article presents a theoretical model for the formation of a dead core within catalyst pellets. The model investigates the nonlinear reaction-diffusion equations governing reactions within catalyst pellets, focusing on the spatial distribution and transformation of substances. To address the complexity of these equations, the Akbari-Ganji Method (AGM) is employed to obtain analytical solutions for reactant concentration, temperature, and effectiveness factor across various geometries. The analytical solutions are validated against numerical solutions obtained using MATLAB, demonstrating excellent agreement. Key findings include the precise characterization of dead core properties, supported by tables and figures. The exact result for limited cases like non-dead core and isothermal reaction conditions is also found, discussed, and confirmed with the main finding